Effectiveness of Safety Helmet Use Policy in Reducing Traffic Accident Rates (Study at Semarang Police Traffic Unit) - Brilianto, Reyhan; D.Djunaedi, D.Djunaedi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. In Indonesia, motorcycles are the main mode of transportation that is widely used because of its economical and efficient nature. Data shows that the majority of vehicles that pass through the highway are motorcycles. However, the high number of these two-wheeled vehicles is also one of the dominant factors contributing to accidents. Accidents involving motorcycles not only cause material losses but also significant fatalities. This makes the safety of motorcycle users a top priority in traffic management. However, in reality, the implementation of this regulation still faces various challenges. There are still many motorcyclists who ignore the obligation to wear helmets, either because of ignorance, indifference, or even because of a lack of awareness of the importance of safety. This phenomenon reflects a gap in the implementation of traffic safety policies. Helmets are often only used as a formality to avoid legal sanctions, not as a safety tool whose benefits are understood and appreciated. This shows the need for more intensive law enforcement and ongoing education for the community. The increasing trend in the number of accidents involving helmet use was also recorded in 2023, which was 1,153 cases, with 126 fatalities, 1 serious injury, and 1,098 minor injuries. Meanwhile, for accidents without helmet use, the number reached 103 cases, with 25 fatalities, no serious injuries, and 85 minor injuries. These data show that although the number of accidents involving helmet users is higher overall, the fatality rate for helmet users is relatively lower compared to victims who do not wear helmets. In 2024, there was another increase in accidents involving helmet users of 1,339 cases, with 121 fatalities, 1 serious injury, and 1,240 minor injuries. Meanwhile, accidents without helmet use were recorded at 102 cases, with 22 fatalities, no serious injuries, and 88 minor injuries. The same pattern can be seen, where fatalities from the group not wearing helmets remain proportionally higher than those wearing helmets.